2021
DOI: 10.1088/2057-1976/ac3197
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced airway changes and downstream ventilation decline in a swine model

Abstract: Purpose. To investigate indirect radiation-induced changes in airways as precursors to atelectasis post radiation therapy (RT). Methods. Three Wisconsin Miniature Swine (WMS TM ) underwent a research course of 60 Gy in 5 fractions delivered to a targeted airway/vessel in the inferior left lung. The right lung received a max point dose <5 Gy. Airway segmentation was performed on the pre- and three months post-RT maximum inhale phase of the four-dimensional (4D) computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…We believe this to be indication of an "indirect effect" where regions receiving no or minimal dose experience large functional declines. This effect has been observed previously in several studies (Wallat et al, 2021) (Vicente et al, 2020) (Thomas et al, 2019) (Farr et al, 2018).…”
Section: Figure 11supporting
confidence: 86%
See 2 more Smart Citations
“…We believe this to be indication of an "indirect effect" where regions receiving no or minimal dose experience large functional declines. This effect has been observed previously in several studies (Wallat et al, 2021) (Vicente et al, 2020) (Thomas et al, 2019) (Farr et al, 2018).…”
Section: Figure 11supporting
confidence: 86%
“…To do this, detailed dose response models are required. In recent years, multiple groups have begun developing these models and some have tested their efficacy in clinical trials ( McDonald et al, 1995 ) ( Mah and Dyk, 1988 ) ( Mehta, 2005 ) ( Graves et al, 2010 ) ( Patton et al, 2018 ) ( Koike et al, 2015 ) ( Hopkins et al, 2012 ) ( Zhang et al, 2010 ) ( Vinogradskiy et al, 2013 ) ( Wallat et al, 2020 ) ( Wallat et al, 2021 ) ( Bates et al, 2009 ) ( Hoover et al, 2014 ) ( Ireland et al, 2016 ) ( Vicente et al, 2020 ). To date, the only prospective clinical trials using these techniques have been ventilation-based ( Bayouth et al, 2019 ) and all non-contrast CT-derived methods have been exclusively ventilation based ( Patton et al, 2018 ) ( Vinogradskiy et al, 2013 ) ( Vicente et al, 2020 ) ( Castillo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this work was done using SPECT, which has the issue of producing low-resolution images prone to artifacts and attenuation, making the nuances of the indirect effect difficult to localize [ 23 , 25 , 26 , 27 ]. Wallat et al presented the first CT-derived evidence of there being an indirect effect, focusing on post-RT ventilation change due to damage to the airways [ 28 ]. Vicente et al later developed a functional avoidance technique that incorporated this indirect ventilation effect and found that the average predicted ventilation preservation was 14.5% higher than conventional RT techniques and 11.5% higher than functional avoidance algorithms that consider only local damage [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subject weights ranged from 70 to 100 kg. Our group has previously used WMS for pre-clinical studies ( Wallat et al., 2021 ; Wuschner et al., 2021 ; Wuschner et al., 2022a ; Wuschner et al., 2022b ).…”
Section: Methodsmentioning
confidence: 99%